Design and optimization of secant pipe roofing structure applied in subway stations. (May 2023) - Lu, Bo; Zhao, Wen; Wang, Wentao; Jia, Pengjiao; Du, Xi; Cao, Wenxin; Li, Weiwei
Graphical abstract: Highlights: A combined experimental and numerical investigation on the flexural behavior of SPR structure is presented. The practical equations for predicting the flexural stiffness and ultimate capacity of SPRs are established. The structural parameters are optimized using fuzzy mathematics theory. Abstract: A secant pipe roofing (SPR) structure is a novel pipe roofing structure with considerable potential as a supporting structure for subway stations, whose structural system affects the bending loading conditions during construction. Therefore, it is essential to conduct further flexural research. However, minimal research has focused on the flexural behavior of SPR structures; in addition, the influence of parameters remains unclear and optimal parameter combinations remain lacking. Hence, the main purpose of this study was to investigate the flexural performance of the SPR structure and establish a finite element (FE) model with precise material constitutive models to optimize the parameters. First, the flexural behavior of the SPR structure was investigated using flexural tests. During the entire loading process, all specimens exhibited ductility, with the specimens' three stress phases and failure mechanisms discussed and clarified based on the experimental results. Subsequently, 16 sets of FE models were built to study the effects of the parameters on the ultimate capacity, deformation, and cost of the SPR structure. Furthermore, the calculations of the ultimate capacity and SPR flexural stiffness obtained using the proposed formulas were consistent with the experimental results and numerical simulations. Finally, a combination of different parameters was optimized using the fuzzy mathematical theory. The optimal parameter combination is a steel pipe diameter: steel pipe thickness: steel bar diameter: adjacent steel pipes' overlapping length is 1:0.03:0.04:0.37. These results are expected to provide a reliable reference for the design and application of SPR structures.